Microstructure and mechanical properties of magnesium matrix composite reinforced with carbon nanotubes by ultrasonic vibration - Li, Cheng-Dong; Wang, Xiao-Jun; Liu, Wei-Qing; Wu, Ku; Shi, Hai-Long; Ding, Chao; Zheng, Ming-Yi (Rare metals, 2022)
A novel approach was successfully developed to fabricate bulk carbon nanotube-reinforced Mg matrix composites with uniform carbon nanotubes (CNTs). The approach consists of pre-dispersion and ultrasonic vibration. Homogeneous and single CNTs on flake Zn powder can be achieved simply by slurry blending. The pre-dispersed CNTs were added to Mg melt, and then, the melt was ultrasonically processed. After ultrasonic vibration, the CNTs/Mg–6Zn melt was cast into a metal mold. Most CNTs distribute homogeneously and singly in the bulk composites. Moreover, good interfacial bonding is achieved, and Raman spectroscopy analysis shows that the damage to CNTs is insignificant. Meanwhile, CNTs evidently improve the ultimate tensile strength, yield strength and elongation. The Kelly–Tyson formula agrees well with the experimental tensile value, and the load-transfer efficiency is nearly equal to 1.